The Association of Arterial Shear and Flow-mediated Dilation in Diabetes - Gibbs, Bethany Barone (Vasc Med, 2011)
While adjusting flow-mediated dilation (FMD), a measure of endothelial function, for shear rate may be important when evaluating endothelial-dependent vasodilation, the relationship of FMD with shear rate in study populations with cardiovascular risk factors is unclear. We aimed to investigate the association of 4 measures of shear rate (peak shear rate (SR(peak)) and shear rate area under the curve through 30 seconds (SR(AUC 0-30)), 60 seconds (SR(AUC 0-60)), and time to peak dilation (SR(AUC 0-ttp))) with FMD in 50 study subjects with type 2 diabetes and mild hypertension undergoing baseline FMD testing for an exercise intervention trial. Associations among measures of shear rate and FMD were evaluated using Pearson's correlations and R(2). The 4 measures of shear rate were highly correlated within subjects, with Pearson's correlations ranging from 0.783 (p<0.001) to 0.972 (p<0.001). FMD was associated with each measure of shear rate, having a correlation of 0.576 (p<0.001) with SR(AUC 0-30), 0.529 (p<0.001) with SR(AUC 0-60), and 0.512 (p<0.001) with SR(peak). Nine of 50 subjects (18%) did not dilate following the shear stimulus. Among the 41 responders, FMD had a correlation of 0.517 (p<0.001) with SR(AUC 0-ttp) and similar correlations to those found in the full sample for SR(AUC 0-30), SR(AUC 0-60), and SR(peak). In conclusion, shear rate appears to explain up to a third of between-person variability in FMD response and our results support the reporting of shear rate and FMD with and without adjustment for shear rate in similar clinical populations with CVD risk factors.